THE INFLUENCE OF CULTURE ORGANIZATION,CAREERDEVELOPMENT, WORK ENVIRONMENT, COMPENSATION POLICY AND ATTITUDE OF EMPLOYEES OF THE WORKING LIFE QUALITY ON THE ENVIRONTMENT OF THE SECRETARIAT OF COORDINATING MINISTRY FOR ECONOMIC AFFAIRS - Agung Setywan (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
Based on the condition and circumstance of quality of work life at  the Secretariat of the Coordinator Ministry for Economic Affairs, Jakarta, which is based on preliminary research show its not satisfactory, the purpose of this study was to: (1) determine the influence of organizational culture on quality of work life, (2) the effect of career development on the quality of work life, (3) the effect of the work environment on the quality of work life, (4) the effect of compensation policy and benefit on the quality of work life, and (5) the effect of employee attitudes to job towards the quality of working life. Methodologically, the research approach is a quantitative approach. The method research instrument is a questionnaire containing 89-point declaration from the six latent variables in the study, using the Likert Scale 1-5. The independent latent variable is the quality of work life, while independent latent variables are organizational culture, career development, work environment, compensation policy and benefit, and employee attitudes to work. Location of the study at the Secretariat of the Coordinator Ministry for Economic Affairs, Jakarta, with a population of 116 employees.Data were analyzed using Partial Least Square (PLS) Structural Equation Modeling (SEM), with software SmartPLS 3. The result showed that the fifth independent variable only one influential positive and significant on the quality of working life Which means the fifth independent variable having value predictive (predictive relevance) on the quality of working life.Meanwhile the fifth regression variable indepedenshow different results: ( i ) insignificant between cultures organization with the quality of working life, ( ii ) there is a positive connection between development and significant career with the working life , ( iii ) insignificant between the workplace with the working life , ( iv ) insignificant policy of compensation and benefit with the working life; ( v ) insignificant between the employees to the quality of working life.  Keywords:   Quality of work life, cultural organization, career development, work environment, compensation policy and benefit, employee attitude to work.